Kinetics of intestinal replication of group B rotavirus and relevance to diagnostic methods. - Vonderfecht, S L (1988)
Non-group-A rotaviruses have been implicated with increasing frequency as causes of acute gastroenteritis in humans and other animals. However, the incidence and significance of infection with these agents, as well as appropriate diagnostic strategies for making these determinations, are largely unknown. Studies to make these determinations could be more accurately conducted if the relationship between the viral replication kinetics and the particular diagnostic method used is understood. We thus utilized the murine model of group B rotavirus infection to establish the viral replication kinetics by a variety of commonly used diagnostic methods. Enzyme immunoassay, routine negative-stain electron microscopy, solid-phase immunosorbent electron microscopy, polyacrylamide gel electrophoresis, and a dot hybridization assay were used in these studies. By enzyme immunoassay, 100% of experimentally infected suckling rats tested positive for group B rotaviral antigens at 1, 4, and 5 days postinoculation. However, only 70 and 20% of infected animals tested positive at days 2 and 3 postinoculation, respectively. Dot hybridization with a complementary DNA probe also suggested a biphasic pattern of viral antigen excretion. Evidence of the virus causing infectious diarrhea in infant rats was found only on day 1 postinoculation in samples examined by routine negative-stain electron microscopy and by polyacrylamide gel electrophoresis. Rotaviruslike particles were observed by solid-phase immunosorbent electron microscopy on days 1, 2, and 4 after viral inoculation suckling rats but were clearly the most numerous on day 1. Additionally, the enzyme immunoassay was used to quantitate the kinetics of group B rotaviral replication in the intestines of the experimentally infected animals. Levels of murine group B rotaviral antigens in intestinal samples peaked on days 1 and 4 postinoculation; however, only peak 1 represented actual intraepithelial replication of the virus. These studies thus indicate that early sample collection and selection of the appropriate diagnostic method are critical if the incidence and significance of group B and possibly other non-group-A rotaviral infections are to be accurately assessed.